THE SOCIETY OF MIRRORS: CRITICAL DIALOGUES WITH THE ESSAY “THE EXPULSION OF THE OTHER: SOCIETY, PERCEPTION AND COMMUNICATION TODAY”, BY BYUNG-CHUL HAN (2024) - Oliveira , Lucas Sávio Freire da Silva (LUMEN ET VIRTUS, 2025)
This manuscript establishes critical dialogues with one of the most prestigious essays by South Korean philosopher Byung-Chul Han, entitled ‘The Expulsion of the Other: Society, Perception and Communication Today’ - first published in 2016 by Matthes & Seitz Berlin Verlagsgeselischaft mnH., under the title ‘Die Austreibung des Anderen - Gesellschaft, Wahrnehmung un Kommunikation heute’. Based in Germany, where he teaches and does scientific research at the Berlin University of the Arts, in this essay the author continues his reflections on the dynamics between man and society, with an emphasis on the relationships between subjects and the association of enslavement that the subject maintains in the face of the capitalist system. It is through this lens that Han discusses the reproducibility of equals in a society that no longer makes room for differences, strangeness and authenticity. Perhaps, in ‘The Expulsion of the Other’, Han manages to complement his elucidations in ‘The Burnout Society’ and ‘Palliative Society: Pain Today’ - masterpieces of his career - by asking: where will we end up in a world where the existence of the genuine ‘I’ is impossible?